Reuse of aluminosilicate industrial waste materials in the production of alkali-activated concrete binders - Payá, J.; Monzó, J.; Borrachero, M. V.; Tashima, M. M. [UNESP] (Elsevier, 2014)
The use of alternative inorganic waste materials, other than fly ashes or blast furnace slag, in the production of alkali-activated binders is reported. Residues from industrial activities related to energy, metallurgy, mining, ceramics, construction and demolition, chemical and petrochemical industries and agro-industry are described. For each waste material, the main chemical, physical and mineralogical characteristics are summarized. Additionally, some mechanical and microstructural properties of paste, mortar or concrete prepared by alkali activation of these residues are presented.
Keywords: Agrowaste ash; Construction and demolition waste; Fuel and municipal waste ash; Mining and industrial waste; Non-ferrous slag